Childhood Passive Smoking Exposure and Age at Menarche in Chinese Women Who Had Never Smoked: The Guangzhou Biobank Cohort Study. - Shanshan Yang; Yali Jin; Yao He; Chaoqiang Jiang; Kar Keung Cheng; Weisen Zhang; Tai Hing Lam (PLoS ONE, 2015)
We examined the associations between childhood passive smoking exposure and age at menarche in women who had never smoked in southern China.Among 30,518 participants in Guangzhou Biobank Cohort Study (GBCS) from 2003-2008, 20,061 women who had never smoked and had complete outcome data were included. Childhood passive smoking exposure was defined as living with 1 or more smokers in the same household during childhood. Data on the number of smokers in the household and frequency of exposure (density and frequency) were also obtained. Age at menarche was measured as a continuous variable.11,379 (56.7%) participants were exposed to passive smoking during childhood. Compared to those with no passive smoking exposure during childhood, those with exposure ≥ 5 days/week had menarche 0.19 year (95% confidence interval (CI): 0.13-0.25) earlier on average. Those exposed to more than two smokers had menarche 0.38 year earlier (95% CI: 0.29-0.47). Childhood exposure was associated with early age at menarche (≤ 13 vs. >13 years), with an adjusted odds ratio of 1.34 (95% CI: 1.21-1.48) for high density, and 1.17 (95% CI: 1.09-1.26) for high frequency of exposure.Childhood passive smoking exposure was associated with earlier age at menarche, with a dose-response relationship in Chinese women who had never smoked. If causal, the results support the promotion of smoking cessation in families with children, particularly young girls.